دراسة وحل مشكلة تنشية الخيط القطني نمرة 12 انكليزي في شركة نسيج اللاذقية - مها سليمان (Tishreen University, 2017)
خضعت الأقمشة المنسوجة في العقود الأربعة الماضية إلى منافسة هائلة من قبل أقمشة الموضة, الأقمشة المحاكة, واللامنسوج. وقد قابل صناع النسيج ضغط المنافسة بالتركيز على تصميم أنوال توفر سرعات عالية نسبياً. ولتلبية متطلبات الإنتاجية العالية على آلات النسيج يجب تحسين خصائص المادة الأولية, وجودة وفعالية تحضيرات النسيج. ويتم هذا التحسين بتغطية الغزل بطبقة من النشاء قبل النسيج وذلك في عملية التنشية التي تعتبر قلب عملية النسيج. يهدف هذا البحث إلى دراسة العوامل المؤثرة أثناء عملية التنشية على نوعية الخيط القطني وتحديد القيم المثلى لهذه العوامل حيث تبين خلاله تأثير سرعة آلة التنشية على زمن بقاء الغزل داخل محلول التنشية و بالتالي على تحميله بالنشاء, ومن جهة أخرى تبين تأثير ضغط اسطوانات العصر في آلة التنشية وكذلك لزوجة محلول التنشية في نسبة تحميل الخيط بالنشاء مما يؤثر لاحقاً على احتماله للقوى المؤثرة عليه أثناء النسيج ثم الاستعمال كخيط ضمن قماش لاحقاً لأن نجاح عملية التنشية هو نجاح للعمليات اللاحقة وهي النسيج والتجهيز النهائي, وغيرها. In the past four decades, the woven fabrics has been subject to inordinate competition which has primarily come from the fashion (short runs), knitting, and nonwoven segments. The weaving machinery manufacturers answered the pressure of competition by concentrating on the design of looms that offered relatively very high speeds. Obviously, to meet the demands of the higher productivity on the loom, the material characteristics and the quality and efficiency of the preceding processes also needed to be improved. And this improvement is doing by encapsulate the yarn with size film before weaving, by the sizing process which considered as the heart of weaving. this research is aimed to studying the affective factors of sizing, and define the ideal values of it. This research reffered to the effect of sizing machine speed on yarn size witting time and then on its coating percent, other side the rollers squeezing pressure of sizing machine and sizing solution viscosity affect on yarn size coating percent too which affecting on its resistance toward weaving operation and usage later, because , the success of sizing process leads to success the following stages like, weaving, finishing, and then, success in fabric usage.